ICESat-2 Reveals Accelerated Global Glacier Mass Loss Except Alaska From 2019 to 2023 - Yubin Fan; Lanhua Luo; Chang-Qing Ke; Genyu Wang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The estimation of the worldwide glacier mass balance between 2019 and 2023 was accomplished through the utilization of ICESat-2 ATL06 data by employing a quadratic surface model fitting approach. Glaciers have a mass change of −331.68 ± 59.07 Gt/yr during this four-year span, which can be equivalated to a sea level rise of 0.916 ± 0.163 mm/yr. Accelerated but contrasting patterns of glacier mass change have been observed, with an accelerated mass loss found in regions such as Svalbard, Russian Arctic, the High Mountain Asia, and the southern Andes. In contrast, Alaska exhibited a decelerated mass loss, and some Antarctic glaciers experienced a slight mass gain. In the maritime regions, land-terminating glaciers have experienced more extensive mass loss except Svalbard and the Russian Arctic. The analysis of seasonal glacier changes indicated that the majority of regions demonstrated their lowest glacier mass in the summer of 2022, and lost approximately 50% mass during 2022–2023. These results provide valuable reference data for the assessment of glacier mass balance using ICESat-2.